Grade III bilateral trigger thumbs treated by prolotherapy: a case report (World Journal of Current Medical and Pharmaceutical Research, 2022)
Introduction: Trigger Thumb is a condition that is caused by a thickened A-1 pulley, often secondary to a stenosed tendon sheath. There are several treatment options for trigger thumb, yet the use of prolotherapy to treat Trigger Thumb has not been widely discussed in the literature. Therefore, this study aims to present the case of Bilateral Trigger Thumbs which were treated using Prolotherapy.Case: A 49-year-old female patient was admitted to the hospital with a complaint of inability to flex his both left & right thumbs two months ago. On physical examination, there was pain and swelling at the base, palmar side of his both thumbs, tender in consistency, and warm. There was a pain in daily activities using his both hands. There wasn’t a history of trauma. The range of motion of both thumbs was decreased. The prolotherapy was given to the right thumb, yet the left thumb was treated by lidocaine injection only. After several treatments using prolotherapy, the right thumb showed better results compared to the left by increasing ROM, decreasing pain level and swelling, and the improving function of the right thumb.Conclusion: In this case, the right thumb, which was treated with prolotherapy, has shown better results compared to the left thumb which was treated with medication only. We suggest prolotherapy to treat trigger fingers for the other patients in our hospital.